Shakespeare and Seriality (Bloomsbury Academic, 2025)
Encompassing a wide variety of genres, media and art forms across a broad historical scope, this open access book identifies central strategies of serialization in Shakespeare’s plays and their adaptations. Beginning with an introduction that theorizes the method of reading Shakespeare serially on page, stage and screen, the first section investigates Shakespeare himself as a serial writer and serial rewritings of Shakespeare by Joyce and Beckett. Shakespeare and Seriality then moves to a series of case studies of performative seriality from the early modern stage to theatre, film and ballet in the 20th and 21st centuries. It culminates in the analysis of adaptations of Shakespeare in complex TV series, including Succession, the postapocalyptic series Station Eleven and the cosy crime series Shakespeare and Hathaway. This book investigates Shakespeare’s seriality from various theoretical perspectives and through multiple methods, including gender and queer theory, ecocriticism, memory and heritage studies, psychoanalysis, empathy studies and fandom studies, reception history and theatre history. Examining serial reading as a method of establishing intertextual and intermedial links, this volume contributes to recent developments in adaptation studies including the debate between Shakespeare and ‘not-Shakespeare’. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Centre of Cultural Inquiry (ZKF) and the Publication Fund of the University of Konstanz.